Mag, wat kan? Over genetische manipulatie* - Schuurman, E. (Koers, 1983)
In the course of the development of technology the ethical question as to whether indeed man "may” do all that he is "able" to do frequently rears its head. In this article ethical issues are raised with regard to the problems surrounding genetic manipulation. Various experiments in the field of genetics, the possibilities of application of these and the ethical responsibility of the scientists involved are discussed. Attention is directed especially at the genetic manipulation of man as in, for example, test-tube baby techniques. A stand is taken against experiments with aborted foetuses, test-tube babies and cloning. Manipulation of the total genetic composition of man is rejected unequivocally.